NMR studies of the dynamics and the folding of hen lysozyme - Buck, M; Buck, Matthias (1994)
﻿ This thesis describes an investigation into the folding behaviour of hen lysozyme by characterisation of the structure and the dynamics of different conformational states of the protein. The native state, a partially structured state generated by the addition of a cosolvent, trifluoroethanol (TFE), and a highly denatured state of the protein in presence of urea at low pH, have been studied at equilibrium by circular dichroism (CD) and nuclear magnetic resonance (NMR) spectroscopy. The principal methods utilised in-fchis thesis are the measurement and interpretation of amide hydrogen exchange and 15 N relaxation data. Amide hydrogen exchange rates from a highly denatured state of hen lysozyme in 8 M urea, at pH 2.0, are well approximated by recent estimates for intrinsic exchange rates from unstructured polypeptides, implying that residual .structures cannot be persistent in this state. In the native protein, by contrast, protection factors are measured to be of the order of 104-108 and can be rationalised by the involvement of amides in secondary structure and burial from the protein surface. Surface accessibility has also been found to be an important determinant of the dynamics of main and sidechain groups monitored by 15N relaxation. For this purpose 15N resonances of native lysozyme were assigned and order parameters derived. The dynamic behaviour was considered in the light of features of the crystal and NMR structures, suggesting that a lack of van der Waals contacts is a major determinant for mobility. A denatured state of hen lysozyme, formed by addition of TFE cosolvent, has been developed as a model for a partially ordered conformation of the protein. Amide hydrogen exchange measurements show that sites with the highest protection factors, up to 250, are located in stable native-like helices. Near complete assignment of 15N-edited NMR spectra allowed a detailed description of secondary structure in the TFE denatured state. Non-native α-helical structure is present as extensions to the native helices and in a region of the polypeptide which forms part of the β-sheet in the native state. These structures have been shown to be in accord with the helical propensities of the primary sequence. Preliminary structure calculations suggest that, despite the absence of extensive and persistent tertiary interactions, topological restraints exist in parts of the TFE denatured state, resulting in considerable propensities for native-like arrangements of the secondary structure. Mainchain dynamics determined by 15N relaxation, although increased in magnitude, appear to be related to that of the native state and are dominated by the position of disulphide bonds and by chain hydrophobicity. Thus the structural and the dynamic behaviour of the polypeptide chain in the TFE denatured state could be rationalised, at least in part, by consideration of features of the primary sequence.